Development, Optimization and Evaluation of Herbal Patch Formulation for Acne Treatment - Patel, Kinjal; Patel, Keyur; Zaveri, Maitreyi (International Journal of Pharmaceutical Investigation)
Background: More than 85% of young people around the world suffer from acne vulgaris, which is the most prevalent chronic inflammatory skin illness. The study’s objective was to develop a herbal patch formulation contained quercetin, curcuminoids, and berberine HCl for the treatment of acne that utilizing ethyl cellulose and HPMC K4M as polymers and propylene glycol as a plasticizer. Materials and Methods: Drug excipient compatibility study was performed using FT-IR. Preliminary trial was done for screening of polymers and plasticizer concentrations. The combined influence of the two independent variables, namely the concentration of HPMC K4M and ethyl cellulose, on the dependent variables, tensile strength and cumulative % drug release at 24 hr, was examined using a 32 full factorial design. Patches were evaluated for physicochemical parameters. Results: Drug excipient compatibility study revealed that drug and excipients are compatible with each other. The optimized formulation (C0) showed tensile strength 2.56 kg/cm2, cumulative percentage drug release of quercetin, berberine HCl, and curcuminoids at 24 hr were 94.02%, 64.66%, and 94.21%, respectively. Tensile strength increased with an amount of HPMC K4M and Ethyl cellulose increases, the cumulative percentage of drug release decreased as HPMC K4M and ethyl cellulose concentrations were raised. Conclusion: Optimized herbal patch formulation had shown good physico-chemical and mechanical properties. The research shows that the developed formulation has the potential to be a useful replacement for the present medications in the market.
Keywords: Acne; Berberine HCl; Curcuminoids; Ethyl cellulose; HPMC K4M; Quercetin.